ANALISIS RISIKO DALAM PROSES PENGADAAN BARANG DI PERUSAHAAN PERMINYAKAN INDONESIA MENGGUNAKAN PENDEKATAN HOUSE OF RISK - Vikaliana, Resista; Nazla, Aisah (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2024)
This study analyzes the risks in the procurement process at ORC using the House of Risk approach. The methodology used in this study includes: identification of various risks related to the procurement process, measurement of the probability of risks, and the impact of designing an effective risk mitigation strategy. Risk identification is carried out through observations, interviews, questionnaires, and literature studies related to practical work topics. The results of the phase 1 HOR analysis identified the five best risk mitigation strategies, namely: clearly informing the requirements and format of the bidding documents they must prepare and providing an easily accessible and understandable written guide on the procurement procedure (PA1), ensuring that the selection criteria for each aspect (administrative, technical, HSSE Plan, and commercial) have been clearly and objectively established before the selection process begins (PA5), ensure the HPS/OE covers all relevant costs, including direct and indirect costs, as well as reasonable profit margins (PA4), ensure the definitive officer has allocated authority or delegation of duties to staff or other officials who may temporarily replace them (PA2), conduct a thorough assessment of the availability of local supplies necessary to meet the TKDN value (PA3). This study provides recommendations to implement identified mitigation strategies and regular monitoring for improved risk control. The results of this study contribute to the development of procurement risk management in ORC and become a reference for decision-making in risk mitigation at the procurement stage.